Interrater Agreement of an Arthroscopic Anterior Cruciate Ligament Tear Classification System. Issue 12 (2nd December 2020) - ,; Vega, José F.; Strnad, Gregory J.; Briskin, Isaac; Cox, Charles L.; Farrow, Lutul D.; Fadale, Paul; Flanigan, David; Hulstyn, Michael; Imrey, Peter B.; Kaeding, Christopher C.; Owens, Brett D.; et al.
Background: Anterior cruciate ligament (ACL) rupture is the most common ligament injury treated surgically by orthopaedic surgeons. The gold standard for the treatment of the majority of primary ACL tears is ACL reconstruction. However, novel methods of repair, such as bridge-enhanced ACL repair (BEAR), are currently being investigated as alternatives to reconstruction. To assess patients for midsubstance repair suitability, clarify the prognostic implications of injury location and damage, and evaluate the results of a repair technique, it is important to have a baseline classification system or grading scale that is reproducible across surgeons, particularly for multicenter collaboration. Currently, no such system or scale exists. Purpose: To develop an arthroscopic ACL tear classification system and to evaluate its interobserver reliability. Study Design: Cohort study (diagnosis); Level of evidence, 3. Methods: Eleven fellowship-trained orthopaedic surgeon investigators reviewed 75 video clips containing arthroscopic evaluation of a torn ACL and then completed the 6-question ACL Pathology Evaluation Form. Agreement statistics including exact agreement, Fleiss κ, Gwet agreement coefficient 1 (AC1), and Gwet AC2 were then calculated to assess interobserver reliability. Results: In aggregate, the multiple assessments of observer reproducibility revealed that surgeon participants in this study, when evaluating the same injury, agreed roughly 80% of the time on whether (1) at least 50% of the tibial footprint remained, (2) the remaining tibial stump was ≥10 mm, and (3) the injury was therefore reparable using the BEAR procedure. Participants also agreed roughly 60% of the time on exactly how many suturable bundles were available. These characteristics are believed to be most important, among those studied, in determining whether a torn ACL is amenable to midsubstance repair. Conclusion: This study is the first of its kind to demonstrate the interobserver reliability of arthroscopic classification of ACL tears. We have demonstrated that this classification system, though not ideally reproducible, is reliable enough across surgeons at multiple institutions for use in multicenter studies. Registration: NCT03776162 (ClinicalTrials.gov identifier).